Wirtschaft, Technik und der herausfordernde Anspruch des Klimawandels - Eine philosophische Betrachtung zu den Wurzeln des anthropogenen Klimawandels - Hans-Jörg Beilharz (IUBH Internationale Hochschule, 2020)
Two important factors influencing anthropogenic climate change are growth in technology and economic activity. By using a philosophical approach, we look at the essences of technology and economics to deeper understand the roots of climate change. According to Heidegger, "modern technology" is a mode of revealing truth by challenging nature. Considering the etymology of economics, we find that the origins of economics lie in supplying and caring. Although their essences are different, the common property of modern technology and economics is the challenging characteristic of their dynamics. Over time, they challenge nature and humans with rising intensity. The dynamics unfolds within a "demand" on us, the humans. Because anthropogenic climate change is a consequence of the increasing intensity in the dynamics of economics and technology, it is also related to a demand we try to satisfy. One possibility to emancipate from the dynamics and to overcome the dangers of climate change is to "hear" the demand and to get into a dialogue about it.
Keywords: A12; Q54; 650; technological and economic growth; climate change